Walking Up The Down Escalator : Public Investment And Fiscal Stability - Easterly, William, 1957- 07.09.1957- (The World Bank, 2007)
Fiscal adjustment becomes like walking up the down escalator when growth-promoting spending is cut so much as to lower growth and thus the present value of future tax revenues to a degree that more than offsets the improvement in the cash deficit. Although short-term cash flows matter, a preponderant focus on them encourages governments to invest too little. Cash flow targets also encourage governments to shift investment spending off budget, by seeking private investment in public projects-irrespective of its real fiscal or economic benefits. To evade the action of cash flow targets, some have suggested excluding from their scope certain investments (such as those undertaken by public enterprises deemed commercial or financed by multilaterals). These stopgap remedies might sometimes help protect investment, but they do not provide a satisfactory solution to the underlying problem. Governments can more effectively reduce the biases created by the focus on short-term cash flows by developing indicators of the long-term fiscal effects of their decisions, including accounting and economic measures of net worth, and where appropriate including such measures in fiscal targets or even fiscal rules, replacing the exclusive focus on liquidity and debt